As parcerias tecnológicas no SUS: o novo marco legal da ciência e tecnologia e as novas oportunidades para FIOCRUZ - Villas Bôas, Paulo de Carvalho (2017)
Purpose - The work consists in the accomplishment of a qualitative study regarding the technological partnerships signed within SUS and the opportunities brought to the Oswaldo Cruz Foundation's partnerships with the advent of the "new legal framework of science and technology" (Law 13243/2016) under the Constitutional Amendment 85/2015. Design/Methodology - In this aim, the work initially seeks to delimit the term "technological partnerships", defining what “technological” activities are and what are considered "partnerships" for the purposes of the study. From the delimitation, the work then places such covenants in the ambit of the SUS, highlighting its relevance in facing the current challenges of the sector, the so-called " challenges of the SUS " (FIOCRUZ, 2015), in which Fiocruz emerges as one of the protagonists. At the end, the study then goes on to identify, from a descriptive and explanatory perspective, the new opportunities that opened up for Fiocruz, as a Public Scientific, Technological and Innovation Institution (ICT) of the SUS, with the new S&T legislation. Findings - From the systematic analysis of the entire normative body modified by the new legal framework, the study identifies the new legal opportunities for Fiocruz and presents a specific contracting model for the Foundation's technological partnerships. Research limitations - The main limitations of the study are the terminological imprecision of the terms "partnership", "technological" and "opportunities", the confidentiality of data and its qualitative nature, which gives a certain degree of subjectivity to its conclusions and propositions. Practical implications- The study presents technical and objective proposals before the new legal perspectives to optimize the use of these instruments in the fulfillment of the institutional mission of Fiocruz. Social implications- The study presents a set of propositions for exploring the entire "mosaic" of new legal opportunities for the benefit of Fiocruz, as a public ICT of the SUS, in the achievement of its institutional mandate and in the best interests of Brazilian public health. Originality - The work deals with an extremely recent legislation with poor specific bibliography, mainly under a Public Administration approach and, to our knowledge, does not have any institutional precedent